Fighting childhood cancer and the innovative project of the Princess Maxima Centre for Paediatric Oncology - Bandeira, Matilde Sá da (2016)
Cancer is one of the most feared diagnoses for the present generations. Yet, for a parent more than for anyone else, knowing that their child has got cancer can be devastating. Childhood cancer is intense and consuming for all people involved, and its physical and psychological consequences are difficult to evaluate. This dissertation aims to understand the main challenges of paediatric cancer, and explore a possible solution to address some of them with a case study: The Princess Maxima Centre for Paediatric Oncology, the Netherlands. To better contextualize the opening of this Centre, a review of literature was conducted to understand the dimension, costs and most important challenges faced by all stakeholders involved. In fact, the project for the Princess Maxima Centre is the Netherlands’ response to some of these challenges. By concentrating all professionals dedicated to this cause, childhood cancer patients and their families in one single building, the Centre aims to cure all children with cancer in the country, but also to make their lives easier. Children will be receiving the most appropriate care as a result of the Centre’s strategy, with particular attention to their natural development. Great accomplishments are expected by all professionals in virtue of the Centre’s environment and therefore better treatment solutions for their patients.